A comparative study on the clinical efficacy of laser hemorrhoidoplasty and rubber band ligation for grade Ⅱ to Ⅲ internal hemorrhoids - Jin Lei; Wu Jiong; Wang Zhenyi; Qin Kaijian; Wu Renjie (结直肠肛门外科)
[Objectives] To compare the clinical efficacy of laser hemorrhoidoplasty (LHP) and rubber band ligation (RBL) in the treatment of grade Ⅱ to Ⅲ internal hemorrhoids. [Methods] From January 2020 to December 2020, a total of 70 patients with grade Ⅱ to Ⅲ internal hemorrhoids were randomly divided into two groups at the Department of Coloproctology, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, each group consisted of 35 cases and received either LHP or RBL treatment. Postoperative anal pain and anal distension (evaluated within 24 hours and on the third day after surgery), wound bleeding (evaluated on the third and seventh day after surgery), postoperative hospital stay, occurrence of postoperative complications within one week after surgery (including dysuria, wound infection, and anal incontinence), and preoperative and postoperative one-month anal resting pressure were recorded. The treatment effectiveness rate and recurrence rate were also evaluated. [Results] The Visual Analogue Scale scores of postoperative anal pain within 24 hours and on the third day were significantly lower in the LHP group than in the RBL group (P < 0.05). The LHP group also experienced milder anal distention (P < 0.05). Wound bleeding on the seventh day after surgery was significantly less in the LHP group compared to the RBL group (P < 0.05), although there was no statistically significant difference in wound bleeding on the third day between the two groups (P > 0.05). Furthermore, the length of postoperative hospital stay was shorter in the LHP group compared to the RBL group (P < 0.05). There were no cases of postoperative wound infection or anal incontinence within one week after surgery in either group. However, mild dysuria was reported by six patients in the RBL group. There was no statistically significant difference in the preoperative and postoperative one-month anal resting pressure within the LHP group or between the two groups (P > 0.05). The postoperative one-month anal resting pressure in the RBL group was higher than before surgery (P<0.05). The treatment effectiveness rate was 100% in both groups, and the recurrence rate did not differ between the two groups (P>0.05). [Conclusion] In conclusion, both LHP and RBL are viable surgical methods for effectively treating gradeⅡ to Ⅲ internal hemorrhoids. LHP can help alleviate postoperative anal pain and anal distension and improve postoperative wound bleeding and is also beneficial for patients to return to normal work and life as soon as possible.